Personality and interest in general practice: results from an online survey among medical students - Maike Krauthausen; Tobias Leutritz; Martin J. Koch; Pamina E. Hagen; Sarah König; Anne Simmenroth (BMC Primary Care)
Abstract Background The growing shortage of General Practitioners (GPs) is a Europe-wide challenge, particularly in rural areas. In Germany, the situation is worsened by an ageing workforce of GPs and insufficient training of new doctors. Many newly qualified physicians choose careers outside primary care or prefer to work part-time to balance work and family life. To address this problem, it is essential to understand the factors that influence medical students’ specialty choice, and then to take action to encourage them to specialise in General Practice (GP). In addition to medical school experiences, rural placements, or characteristics of the specialty, personality traits have been shown to influence students’ specialty decisions. A well-researched approach to assessing personality is the Five-Factor Model, which measures personality on the dimensions openness (to experience), conscientiousness, extraversion, agreeableness, and neuroticism. Using the findings about the links between students’ personalities and an increased interest in a career in General Practice may be an approach to raising the number of GPs. Objectives We aimed to examine how students’ personality traits influence their interest in General Practice and their current intention to pursue General Practice as a specialty. Methods In March 2021, we started an ongoing online survey among medical students at the University of Würzburg and assessed cross-sectional data about the ‘Big Five’ personality traits and aspects of career choice. Until December 2022, we invited three cohorts of first-year beginners, and one cohort each of third-, fifth- and sixth-year students via email to participate in the survey. For statistical analysis, we performed linear regression and extended it into a path model to examine the relationship between students’ personality traits, their interest in General Practice, and whether they would currently choose General Practice for their future specialty. We controlled for possible confounding effects of age, gender, and current semester by using covariates. Results Higher levels of agreeableness and neuroticism predicted greater interest in GPs, whereas higher levels of conscientiousness and openness predicted less interest in GPs. The effects of extraversion were unclear. Age was a significant predictor of interest, with older age associated with greater interest in General Practice. Gender was not a significant predictor of interest in General Practice, and the results for semester were inconclusive. The interest in General Practice is a predictor of the intention to choose GP as a specialty. The personality dimensions show an indirect predictive effect on the intention to choose GP, mediated by interest in GP. In total, R² = 7.7% of the variance of the interest in GP was explained by the combination of personality dimensions and covariates. Conclusion Our study reveals that students’ personality traits predict their interest in General Practice and their intention to choose it as a specialty. Personality assessments can be integrated into counselling services to help students better understand their traits. Our findings highlight the great potential of considering personality in career counselling during medical education or even the extent of admission criteria to medical school by personality-related criteria.